Die Arbeitszufriedenheit von Berufseinsteigern in den Gesundheitsberufen = Job satisfaction of young professionals in health care - Ulrich, Gert; Homberg, Angelika; Karstens, Sven; Götz, Katja; Mahler, Cornelia (Das Gesundheitswesen, 2019)
Background Job satisfaction in health care is currently important in view of workforce shortage in the health care area. The purpose of this study was to evaluate job satisfaction in young health professionals and to identify factors possibly influencing overall job satisfaction. Methods About one year after graduating from vocational training, a total of 579 graduates from various health care professions [Nursing (N), Nursing and Geriatric Nursing; Therapy (TP), Physical therapy and Logopaedics; Diagnostics (D), Diagnostic Radiography and Biomedical Science], were invited to participate in an online-survey. Job satisfaction was assessed with the 10-item Warr-Cook-Wall (WCW) job satisfaction questionnaire. Descriptive analysis of the WCW was performed, and the impact of various factors on job satisfaction was determined by stepwise linear regression analysis. Results In total, 189 graduates (N, n=121; TP, n=32; D, n=36) were included in data analysis (32.6% response rate). Overall job satisfaction in all young professionals was 4.9 +/- 1.6 (mean +/- SD) and was slightly higher in TP (5.4 +/- 1.4) compared with N (4.7 +/- 1.6) and D (5.0 +/- 1.5), respectively. Highest satisfaction was identified with colleagues and lowest satisfaction with income was identified in all professional groups. Colleagues and fellow workers showed the highest score of association regarding overall job satisfaction in regression analysis. Conclusions As a whole, our data suggest good to very good satisfaction in various WCW items of job satisfaction. Colleagues were shown to have a high impact on job satisfaction. To improve the attractiveness of job profiles in health care, the presented results may provide a valuable input regarding workforce shortage.
29. Mai 2017 (eFirst)
Gesehen am 05.06.2019